Contribution to the knowledge of hoverflies (Diptera: Syrphidae) of Macedonia - Krpač, Vladimir (Acta entomologica slovenica (Ljubljana), 2001)
Analysis of material from the Republic of Macedonia shows the presence of 13 species of hoverflies, registered for the first time: Cheilosia antiqua, Cheilosia orthotricha, Cheilosia rhynchops, Chrysotoxum fasciolatum, Chrysotoxum verralli, Merodon alexeji, Merodon recurvus, Merodon rufus, Myolepta potens, Neoascia annexa, Neoascia obliqua, Neoascia unifasciata and Sphegina sublatifrons.
Keywords: Diptera; dvokrilci; favna; Makedonija; Republic of Macedonia; zoologija; zoology; žuželke